Surgical reconstruction of a composite nasomaxillary and superior labial defect in a dog with a fascia lata graft, titanium mesh implant and angularis oris axial pattern flap - Tu, Tsung-Han; Thatcher, Graham P.; Soukup, Jason W. (Frontiers in Veterinary Science, 2024)
Objective: To document the successful surgical reconstruction of a composite nasomaxillary and superior labial defect using a fascia lata graft, titanium mesh and angularis oris axial pattern flap in a dog.An estimated 2-year-old female intact mixed-breed dog was presented with a composite (hard and soft tissue) nasomaxillary defect, suspected to be caused by a chemical burn. Physical examination revealed nasal discharge, exposed bilateral maxilla and nasal bone, nasomaxillary fistula with air movement, and intrinsic discoloration of the left maxillary canine tooth. The soft tissue lesion extended from the nasal planum rostrally to the medial canthus of the left eye distally and from the right maxillary bone to include a full thickness loss of the left maxillary labium laterally. Computed tomographic images of the head showed chronic osteomyelitis of the maxilla, zygomatic and nasal bones with nasomaxillary fistula and numerous exposed roots of the left maxillary premolars. Staged surgical procedures to address the dentition and nasomaxillary defect were planned. The first procedure consisted of the extraction of periodontally compromised left maxillary premolars, and standard root canal therapy of bilateral maxillary canine teeth. The second procedure consisted of debridement of the non-vital soft and hard tissues and surgical reconstruction of the nasomaxillary defect after virtual surgical planning. Head computed tomography performed five months post-operatively revealed a decrease in the size of the osseous defect as well as the resolution of rhinitis.Clinical Relevance: This case demonstrates the feasibility of using a combination of soft tissue graft, titanium mesh, and axial pattern flap in managing nasomaxillary defects. Such defects can lead to chronic rhinitis, infection, discomfort, and long-term morbidity. This case report provides a novel but practical approach for managing defects in the nasomaxillary region in dogs.